Onset of additional plasmon resonances in small sheathed particles - Lerman, L. B. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2008)
Basing on general relations for determination of polarizability for laminated ellipsoid, an analytical investigation has been fulfilled of the equation for determination of plasmon resonance frequencies in case of sheathed particles. Three cases of particle structure are considered: a dielectric kernel with a metal shell; a metal kernel with a dielectric shell; a metal kernel with a metal shell. When calculated dielectric functions are described the Drude model.